Postictal Magnetic Resonance Imaging Changes Masquerading as Brain Tumor Progression: A Case Series - Dunn-Pirio, Anastasie M. (Case Rep Oncol, 2016)
Seizures are common among patients with brain tumors. Transient, postictal magnetic resonance imaging abnormalities are a long recognized phenomenon. However, these radiographic changes are not as well studied in the brain tumor population. Moreover, reversible neuroimaging abnormalities following seizure activity may be misinterpreted for tumor progression and could consequently result in unnecessary tumor-directed treatment. Here, we describe two cases of patients with brain tumors who developed peri-ictal pseudoprogression and review the relevant literature.